Mie Ayam Rasa Nusantara: Perpaduan Tauco Khas Cianjur dalam Konsep Fusion Food - Ismawati; Priatini, Woro; Bridha, Risya Ladiva (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This research is motivated by the declining existence of Cianjur's signature tauco among the community. With the modification through the concept of fusion food between Cianjur's signature tauco seasoning and chicken noodles, it is expected to increase the public's appeal to Cianjur's signature tauco. This study uses a quantitative approach with an experimental method of three recipe formulations with a ratio of tauco seasoning and yellow chicken noodle seasoning, including MAT 1 (50%:100%), MAT 2 (75%:100%), and MAT 3 (100%:100%), followed by organoleptic testing on 30 semi-trained panelists and 100 consumer panelists. Furthermore, the data were analyzed using descriptive statistics. The results of the study showed that MAT 3 was chosen as the standard recipe, and the characteristics of taste, aroma, color, texture and appearance of the tauco chicken noodle product were very well received by consumers. The packaging used is an oval-shaped food container with baggase material. The assessment of the packaging used in the tauco chicken noodle product resulted in a positive assessment..